2011
DOI: 10.1177/0956797611419304
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Interference Between Statistical Summary Perception and Statistical Learning

Abstract: The visual system is an efficient statistician, extracting statistical summaries over sets of objects (statistical summary perception) and statistical regularities among individual objects (statistical learning). Although these two kinds of statistical processing have been studied extensively in isolation, their relationship is not yet understood. We first examined how statistical summary perception influences statistical learning by manipulating the task that participants performed over sets of objects contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 28 publications
4
43
2
Order By: Relevance
“…Indeed, there is compelling evidence that learners can exploit more than one source of statistical information at the same time (e.g. [55,56,59]), although sometimes at the cost of interference [60]. 5 Because sensory information related to SL phenomena is mostly visual or auditory, the tactile modality is omitted for the sake of simplicity.…”
Section: Endnotesmentioning
confidence: 99%
“…Indeed, there is compelling evidence that learners can exploit more than one source of statistical information at the same time (e.g. [55,56,59]), although sometimes at the cost of interference [60]. 5 Because sensory information related to SL phenomena is mostly visual or auditory, the tactile modality is omitted for the sake of simplicity.…”
Section: Endnotesmentioning
confidence: 99%
“…Behaviourally, these two types of statistical learning appear to operate under different constraints (e.g. [26,28,29]), and to mutually interfere with each other such that detecting one kind of structure impairs detection of the other kind [30]. Perhaps related to or emerging from this interference, the time course of the detection of conditional and distributional regularities also differs.…”
Section: Statistical Learning: One Mechanism or Many?mentioning
confidence: 99%
“…On the other hand, studies have shown that the training task sometimes modulates what is learned. For example, when performing a task that extracts the “summary statistics” of an array of lines (e.g., the average orientation), participants fail to learn the co-occurrence of lines on that array (Zhao, Ngo, McKendrick, & Turk-Browne, 2011). In addition, spatial context learning of a visual display shows limited or no transfer between visual search and change detection tasks (Jiang & Song, 2005).…”
mentioning
confidence: 99%